The Improvement Of The Agriculture Based On Market Relations In Karakalpakstan - G.E. Toreniazova (Journal of Learning on History and Social Sciences, 2023)
This study examines the agricultural reforms and challenges in Karakalpakstan, Uzbekistan, from 1993 to 1998. Based on government decrees, statistical data, and archival documents, the research highlights significant developments and obstacles in the agricultural sector. Despite the organization of numerous Dekhan farms and increases in crop production, environmental issues like soil salinity and water mismanagement, exacerbated by the desiccation of the Aral Sea, hindered productivity. The study underscores the need for improved water management, soil quality, and sustainable agricultural practices to enhance productivity and ensure long-term environmental sustainability.